Contribution of Metal Defects in the Assembly Induced Emission of Cu Nanoclusters. - Zhennan Wu; Huiwen Liu; Tingting Li; Jiale Liu; Jun Yin; Mohammed, Omar F.; Bakr, Osman M.; Yi Liu; Bai Yang; Hao Zhang (Journal of the American Chemical Society, 2017)
Aggregation/assembly induced emission (AIE) has been observed for metal nanoclusters (NCs), but the origin of the enhanced emission is not fully understood, yet. In this work, the significant contribution of metal defects on AIE is revealed by engineering the self-assembly process of Cu NCs using ethanol. The presence of ethanol leads to a rapid assembly of NCs into ultrathin nanosheets, promoting the formation of metal defects-rich surface. Detailed studies and computer simulation confirm that the metal defects-rich nanosheets possess increased Cu(I)-to-Cu(0) ratio, which greatly influences ligand-to-metal-metal charge transfer and therewith facilitates the radiative relaxation of excitons. Consequently, the Cu NCs self-assembly nanosheets exhibit obvious emission enhancement.